Strategic leadership and its role in achieving organizational justice in private Yemeni universities from the point of view of academic and administrative leaders - Qaiqab, Fatima Mohammed Maqbool; Al-Amri, Abdulaziz AbdulHadi (Journal of Educational and Psychological Sciences, 2023)
The study aimed to measure the role of strategic leadership in achieving organizational justice in private Yemeni universities from the point of view of the academic and administrative leaders. The study followed the descriptive survey method, and the questionnaire was used as a tool for collecting data from the study sample, which consisted of academic and administrative leaders in (10) private universities, and their number reached (283) individuals, and they represent (77.75%) of the total study population. The results showed that the degree of practicing strategic leadership in all its dimensions was high, with a mean of (3.601), and a relative weight (72.02%(, and the degree of appreciation of the sample members for the level of achieving organizational justice in all its dimensions was medium, with a mean of (3.165), and a relative weight of (63.29%(. The results also showed the existence of a positive, direct, statistically significant correlation between the dimensions of strategic leadership and organizational justice in private Yemeni universities, where the value of the correlation coefficient was (0.867), and there was an effect of the independent variable (strategic leadership) on the dependent variable (organizational justice) with a percentage of (77.70%); The study recomended strengthening strategic leadership practices in private Yemeni universities, espically with regard to investing and developing human capital, and paying attention to the organizational justice approach as one the most important mechanisms that affect the increase in the degree of organizational loyalty among workers, and the development of their creativity and innovation capabilities.
Keywords: Strategic leadership; organizational justice; private universities